Cerebellar tDCS Does Not Improve Learning in a Complex Whole Body Dynamic Balance Task in Young Healthy Subjects - Steiner, Katharina Marie; Enders, Anne; Thier, Wiebke; Batsikadze, Giorgi; Ludolph, Nicolas; Ilg, Winfried; Timmann, Dagmar (PloS one, 2016)
Transcranial direct current stimulation (tDCS) of the cerebellum is of increasing interest as a non-invasive technique to modulate motor performance and learning in health and disease. Previous studies have shown that cerebellar tDCS facilitates reach adaptation and associative motor learning in healthy subjects. In the present study it was tested whether cerebellar tDCS improves learning of a complex whole body motor skill. Because this task involves learning of posture and balance likely including learning of a new motor sequence and cognitive strategies, cerebellar tDCS was applied over midline cerebellar structures and the posterolateral cerebellar hemispheres. 30 young and healthy subjects performed two days of balance training on a Lafayette Instrument 16030 stability platform®. Participants received either anodal, cathodal or sham cerebellar tDCS during training on day 1. The cerebellar electrode (7 cm width by 5 cm height) was centered 2 cm below the inion. Mean platform angle deviation and mean balance time were assessed. All subjects showed significant effects of learning. Learning rate was not different between the three modes of stimulation neither on day 1 nor on day 2. Cerebellar tDCS did not facilitate learning of a complex whole body dynamic balance task in young and healthy subjects. tDCS effects, however, may have been missed because of the small group size. Furthermore, it cannot be excluded that young and healthy subjects learned and performed already at a near optimal level with little room for further improvement. Future work has to evaluate potential benefits of cerebellar tDCS in elderly subjects and subjects with cerebellar deficits, whose motor control and motor learning network is not optimally tuned.